prove that
( n ) . r = n
( r ) Pr Pr
does that make sense?
not sure how to write the question properly
Not sure about your notation, check out the latex tutorial to help write equations more appropriately.
http://www.mathhelpforum.com/math-he...-tutorial.html
Hello deej813
I think you might mean:
$\displaystyle \binom{n}{r}\times\,^r\mbox{P}_r =\, ^n\mbox{P}_r$
In which case, note that $\displaystyle ^n\mbox{P}_r=\frac{n!}{(n-r)!}$
and in particular, if $\displaystyle n = r,\, ^r\mbox{P}_r=\frac{r!}{0!}=r!$, since $\displaystyle 0! = 1$.
Also $\displaystyle \binom{n}{r} = \frac{n!}{r!(n-r)!}$
So $\displaystyle \binom{n}{r}\times\,^r\mbox{P}_r = \frac{n!}{r!(n-r)!}\times r! =\,^n\mbox{P}_r$
Is that it?
Grandad